Multiple Dynamic Targets Encirclement Control of Multiagent Systems. (16th December 2015) - Zhang, Wenguang; Liu, Jizhen; Zeng, Deliang
Abstract : This paper develops the distributed encirclement control problem of multiagent systems, in which each agent tracks multiple targets, each target can be tracked by one agent, and the numbers of the agents and the targets are the same or not. Firstly, an encirclement control protocol is proposed for multiagent systems, and this protocol contains some estimators. Secondly, some conditions are derived, under which multiagent systems can achieve encirclement control by circular formation. Finally, numerical simulations are provided to illustrate the obtained results.